Selective Synthesis of Z‐Cinnamyl Ethers and Cinnamyl Alcohols through Visible Light‐Promoted Photocatalytic E to Z Isomerization. Issue 5 (28th January 2020) - Li, Hengchao; Chen, Hang; Zhou, Yang; Huang, Jin; Yi, Jundan; Zhao, Hongcai; Wang, Wei; Jing, Linhai
Abstract: A photocatalytic E to Z isomerization of alkenes using an iridium photosensitizer under mild reaction conditions is disclosed. This method provides scalable and efficient access to Z ‐cinnamyl ether and allylic alcohol derivatives in high yields with excellent stereoselectivity. Importantly, this method also provides a powerful strategy for the selective synthesis of Z ‐magnolol and honokiol derivatives possessing potential biological activity. Abstract : Photocatalysis : An efficient geometrical E to Z isomerization of cinnamyl ethers and cinnamyl alcohols proceeds through energy transfer using an iridium photosensitizer. A series of contra‐thermodynamic cis ‐cinnamyl ether and alcohol derivatives were achieved through a photoisomerization of the readily available trans ‐isomer. This simple reaction system shows satisfactory Z ‐selectivity, broad substrate scope, and functional group tolerance.